Declining Ungulate Populations in an African Rainforest: Evidence From Local Knowledge, Ecological Surveys, and Bushmeat Records - Kamgaing, Towa Olivier William; Dzefack, Zeun's Célestin Brice; Yasuoka, Hirokazu (Frontiers in Ecology and Evolution, 2019)
Human activities alter the composition and abundance of wildlife populations. A common awareness of these changes by stakeholders, including local people is essential for sustainable management. Hunters (n= 255) from two adjacent community hunting zones (CHZs) in Southeast Cameroon were interviewed about the species composition of the animals caught in snare traps during their beginnings in hunting and in 2015- 2016. The comparison of the trends in game composition to those from transect surveys and bushmeat records conducted in the area since the nineties revealed the followings: (1) hunters are aware of the coarse changes in prey abundance, even for the species for which population density is difficult to estimate using classic survey methods; (2) in southeast Cameroon and in forests regions with similar fauna, the bay duiker and the Peter’s duiker are clearly more abundant than the white-bellied and black fronted duiker; (3) the two sites surveyed are under different stages of prey depletion trajectory, and (4) the ranking of prey abundance by local hunters is consistent with village-based bushmeat records and is likely to reflect more the species compositions in anthropogenic forest mosaics, where hunting pressure is higher. Hunters’ interviews constitute a valuable means to rapidly assess the trends in animal populations. However, the discrepancies between perceptions and prey composition in remote forest areas draw attention to the need of caution when using local knowledge to generalize trends in fauna assemblages over large geographical scales.